Mechanics and analog modeling of the Huo-Ma-Tu thrust sheet in the southern Junggar Basin fold and thrust belt - YANG Geng; CHEN Zhuxin; LU Xuesong; ZHANG Yuqing (Dizhi lixue xuebao)
Objective  Understanding the mechanical development of thrust sheets is fundamental, yet challenging, to comprehensively understand the deformation processes of thrust belts. Various models explain the mechanics behind thrust sheet development, yet significant controversies persist.   Methods  This study takes a comprehensive approach, focusing on the southern Junggar Thrust Belt. We combine a variety of methods including surface geological surveys, seismic reflection profiles, and drilling data analysis with mechanical and physical modeling to thoroughly investigate this issue.   Results  (1) Based on surface geological surveys, seismic data interpretation, and drilling data, we confirm that thrust faults have developed in the core and southern limb of the Huo-Ma-Tu anticline. These faults extend southward beneath the front of anticlines, forming the extensively distributed Huo-Ma-Tu thrust sheet, which exhibits none to weak internal structural deformation. (2) Drilling data from the Huo-Ma-Tu structural belt clearly show that the frontal thrust faults and detachment faults have developed in layers with abnormally high fluid pressure, indicating that the thrust sheet is a combination of strong deformation sheets and weak detachment faults. Analysis of in-situ formation pressure data suggests that the thrust faults within these overpressure layers can segregate fluid pressure coefficients between the hanging wall and the footwall. (3) Using the geometric deformation characteristics of the Huo-Ma-Tu thrust sheet obtained from seismic profiles and drilling data, a simplified mechanical model is established. This model calculates the mathematical relationship between the horizontal compressive stress-to-gravity ratio at the back of the thrust sheet, the geometric parameters of the thrust sheet, the fault friction coefficient, and the fault dip angle. Separate equations are provided for thrust sheets without fluid overpressure and those with fluid overpressure detachment layers. (4) A physical model of the development characteristics of the Huo-Ma-Tu thrust sheet in the Southern Junggar Thrust Belt confirms that the deformation pattern of such rigid thrust sheets aligns with the structural interpretation from seismic profiles. This supports the validity of the simplified mechanical model in reflecting the actual geological conditions.   Conclusions  The simplified mechanical model demonstrates that the required horizontal tectonic stress-to-gravity ratio at the back of the thrust sheet decreases significantly with increasing fluid pressure coefficient. The physical modeling results also verify that the deformation pattern of strong deformation sheets/weak detachment fault thrust sheets generally conform to the structural interpretations of the seismic profiles. The experiments reveal that the large displacements at the base of the thrust sheet result from the accumulation of small-scale displacements coinciding across multiple segments.   Significance  This study proposes simplified rectangular with triangular geometric models of thrust sheets, which can preliminarily explain the kinematics and dynamics of thrust sheets, especially those with fluid overpressure. The derived mathematical relationships accurately describe the geometric, kinematic, and dynamic relationships of thrust sheets and are robustly validated by physical simulation experiments, reinforcing the reliability of our findings.